Isolation of porcine epidemic diarrhea virus strain CHCQ-2023 from Chongqing Province and analysis of S gene recombination - Siying Wang; Xia Hu; Tao Xiong; Lijing Cao; Xingcui Zhang; Zhenhui Song (BMC Veterinary Research)
Abstract Background In recent years, the prevalence and incidence of porcine epidemic diarrhea virus (PEDV) infection have been on the rise. The occurrence of multiviral infections and recombination mutations has led to accelerated viral evolution and reduced vaccine efficacy. In the present study, a PEDV strain was isolated from a pig farm (Chongqing Province, China) with an outbreak of porcine diarrhea, and its S gene was found to be recombinant. Results The optimal trypsin concentration for blind passage of PEDV in Vero cells was determined to be 7.5 µg/mL. Following two blind passages of the virus in Vero cells, the virus was unable to adapt to the cells. Therefore, PEDV was blindly passaged in IPEC-J2 cells using the optimal concentration of trypsin (5 µg/mL). Next, a series of characterization experiments were performed. Recombination analyses of the isolates using software revealed that the S gene of strain CHCQ-2023 was derived from the primary parent strain PEDV-1 C and secondary parent strain SQ2014, with recombination occurring at a 3152 bp breakpoint. Furthermore, a specific B-cell antigenic epitope was predicted on the S2 subunit of the S protein. Conclusion A PEDV strain was isolated and characterized, and its S gene was characterized. The findings provide a bioinformatic basis for the study of PEDV strain variation due to genetic recombination.